Keputusan Pemilihan Strategi Manajemen Laba Pada Perusahaan Yang Mengalami Financial Distress di Indonesia - Setiawan, Putu Ery; Dwiana Putra, I Made Pande (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p05, 2019)
This study discusses real earnings management and classification shifting along with accrual earnings management as an alternative strategy for companies that experience financial distress, and differences in choices of strategies at each stage of financial distress. This research was conducted on all manufacturing companies which experienced financial distress among those listed on the Indonesian Stock Exchange for six years from 2012 to 2017. Purposive sampling was used to collect data from all the manufacturing sector companies listed on the IDX that experienced financial distress. The sample companies totaled to 43 with a total of 258 observation data. The multiple linear regression technique was used in data analysis, analysis aided by SPSS . The results of this study indicate that in the early stages of financial distress, companies tend to choose the real earnings management strategy in the form of decreased production and classification shifting. While in the later stages the chosen strategy is real earnings management through a reduction in selling, general and administrative expenses. Finally at extreme stage, companies tend to adopt income-decreasing accruals strategies Keywords : Financial distress, accrual earnings management, real earnings management, classification shifting